2015
DOI: 10.1007/s10668-015-9706-2
|View full text |Cite
|
Sign up to set email alerts
|

Marginal land use and value characterizations in Lagos: untangling the drivers and implications for sustainability

Abstract: Lagos, the leading African megacity, is a coastal city located in creeks and riparian environment. In all parts of the city, transactions in marginal lands-riparian or water-logged areas-are increasingly becoming more noticeable. However, while previous studies have focused upon normal land transactions, the dynamics of land uses in marginal regions remain largely unexplained. Information on the dynamics of informal land transactions in the marginal regions of Lagos city is important for urban sustainability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Generally, marginal land is defined according to the economic feasibility of land use. Based on the research results of a review of relevant scholars [43][44][45][46][47], we define "marginal land" as idle land that has been vacant for more than three years in rural areas and whose resources are not used for agricultural production, rural planning or other social purposes. Some scholars have found that there is a large waste of marginal land resources in rural China and have put forward that these land resources can be used as rural entrepreneurial development land, but no specific implementation plans for how to use them have been proposed so far.…”
Section: Background and Methods Of Analysismentioning
confidence: 99%
“…Generally, marginal land is defined according to the economic feasibility of land use. Based on the research results of a review of relevant scholars [43][44][45][46][47], we define "marginal land" as idle land that has been vacant for more than three years in rural areas and whose resources are not used for agricultural production, rural planning or other social purposes. Some scholars have found that there is a large waste of marginal land resources in rural China and have put forward that these land resources can be used as rural entrepreneurial development land, but no specific implementation plans for how to use them have been proposed so far.…”
Section: Background and Methods Of Analysismentioning
confidence: 99%
“…The rent bid theory assumes that due to competition, properties at desirable locations attract the highest rents while properties in less desirable locations such as areas at the risk of insecurity attract lowest values (Kauko, 2003; Craig and Hua, 2011; Aliu, 2016). In search for residential homes, both the neighborhood and the dwelling conditions are jointly appraised because they are complementary.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…, 2012; Oloke et al. , 2013; Aliu, 2016; Wu et al ., 2017; Ayedun et al ., 2018; Belanger and Bourdeau-Brien, 2018). In spite of the intensity of studies on the drivers of housing values there is no consensus as to the precise factors that majorly influence home values as scholars differ on the impacts that structural, location and neighborhood factors have on property values.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability comprises three components namely: (I) physical environment (II) economic conditions and (III) social conditions. All mainstream ideas about sustainability share three characteristics: first, sustainability requires integrating policies related to economic development, environmental protection and social justice; second, the interest of future generations is inviolable; and third, transparency and public participation at all levels of decision-making from local to global scale are essential (Aliu, 2016 ; Smets & van Lindert, 2016 ). Sustainable development therefore presupposes the sustainability of natural and artificial resources including sand and the built environment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The National Bureau of Statistics’ population estimates put Lagos Metropolitan Area at 10,778,000 in 2011 and 12,634,000 in 2016 (NBS, 2016 ). Majority of Lagos megacity including the study area is located in riparian water logged coastal environment within sensitive ecological zones which create land management challenges (Aliu, 2016 ).…”
Section: Study Areamentioning
confidence: 99%